Overview Of The Level Of Loneliness Among The Elderly In Harjosari II Village, Medan Amplas District - Ingrid Ameris Putri Andini Zega; Simorangkir, Lindawati; Tumanggor, Lili Suryani (Sean Institute, 2024)
Loneliness is a health problem for the elderly almost all over the world, both in developed and developing countries. Loneliness, if not treated immediately, will have an impact on the quality of life of the elderly. This type of research is descriptive with a cross sectional approach which aims to find out how the level of loneliness in the elderly in Harjosari II Village, Medan Amplas District in 2024. The population in this study is all elderly people in Harjosari II Village, Medan Amplas Dis-trict in 2024, with a sample size of 57 respondents. Purposive sampling technique with the criteria that the elderly do not have complications, do not experience hearing loss and are not senile. Data collection uses a questionnaire. The results of this study showed that of the 57 re-spondents who experienced low loneliness, there were 5 respondents (8.8%), and the elderly who experienced moderate loneliness were 52 respondents (91.2%). The level of loneliness in the elderly greatly af-fects the quality of life of the elderly, the need for family support.